2000
DOI: 10.1136/thorax.55.4.277
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of obstructive pulmonary disease in tunnel workers

Abstract: Background-Tunnel workers are exposed to gases and particles from blasting and diesel exhausts. The aim of this study was to assess the occurrence of respiratory symptoms and airflow limitation in tunnel workers and to relate these findings to years of exposure. Methods-Two hundred and twelve tunnel workers and a reference group of 205 other heavy construction workers participated in a cross sectional investigation. Exposure measurements were carried out to demonstrate the diVerence in exposure between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 22 publications
(26 reference statements)
5
59
2
3
Order By: Relevance
“…Occupational studies have assessed the effects of respiratory toxicants among all workers without limiting to nonsmokers and have controlled for smoking in their models (Beach et al 2001;Gardiner et al 2001;Ulvestad et al 2000). We adopted this strategy and were able to adjust for both current and lifetime smoking history in our models and to conduct an analysis limited to the small number of never smokers in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational studies have assessed the effects of respiratory toxicants among all workers without limiting to nonsmokers and have controlled for smoking in their models (Beach et al 2001;Gardiner et al 2001;Ulvestad et al 2000). We adopted this strategy and were able to adjust for both current and lifetime smoking history in our models and to conduct an analysis limited to the small number of never smokers in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratios (OR) for COPD (GOLD I+ and II+) were calculated for 18 studies. Among the populationbased studies (33-36, 39, 42, 43, 47), OR ranged from 1.08-2.13, and among the studies on inorganic exposure, the OR was 1.70-3.80 (35,40,61,64) and <1 (37), Among the studies on organic exposure, OR ranged from 1.20-8.86 (37,40,75,76) and <1 (35). The data support a "robust" more than a "very strong" (high point estimate of risk) association, but do not contradict a causal relationship.…”
Section: Consistency Strengths and Temporality Of Associationmentioning
confidence: 99%
“…A well-designed community-based study in the United States reported a significantly increased prevalence of COPD among dust-exposed workers (15). Exposure to dust has been associated with COPD in workplaces or occupations such as coal and gold mines (16), tunnel construction (17), concrete manufacturing (18), food processing, bakeries, chemical processing and spray painting (19), and cotton processing, farming, welding, painting, foundry and refractory brick manufacturing (20).…”
mentioning
confidence: 99%